2015
DOI: 10.1159/000442302
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with the Mediterranean Diet Quality Index (KIDMED) among Balearic Islands' Adolescents and Its Association with Socioeconomic, Anthropometric and Lifestyle Factors

Abstract: Background and Aims: To assess the compliance levels of adolescents in the Balearic Islands with the Mediterranean Diet Quality Index (KIDMED Index) and to assess its associations with socioeconomic, anthropometric and lifestyle characteristics. Methods: A cross-sectional survey (n = 1,231; 12-17 years) carried out in 2007-2008. The degree of adherence to the Mediterranean diet (MedDiet) was evaluated using the KIDMED Index. Body composition, body image, socioeconomic factors, and physical activity were also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
2
11
0
2
Order By: Relevance
“…MD adherence widely varied within Mediterranean countries, with large differences also existing among various European countries, while few data are available for non-Mediterranean countries. Similar to our study, studies conducted in Spain, Italy and Greece have confirmed that the majority of children belong to the group of medium adherence to MD (Serra-Majem, 2004;Mariscal-Arcas et al, 2009;Del Mar Bibiloni et al, 2016). To get the insight into the consumption of cereals and bakery products group, the questions dealing with these food groups were extracted from the KIDMED questionnaire and the data obtained are summarized in Fig.…”
Section: Resultssupporting
confidence: 67%
“…MD adherence widely varied within Mediterranean countries, with large differences also existing among various European countries, while few data are available for non-Mediterranean countries. Similar to our study, studies conducted in Spain, Italy and Greece have confirmed that the majority of children belong to the group of medium adherence to MD (Serra-Majem, 2004;Mariscal-Arcas et al, 2009;Del Mar Bibiloni et al, 2016). To get the insight into the consumption of cereals and bakery products group, the questions dealing with these food groups were extracted from the KIDMED questionnaire and the data obtained are summarized in Fig.…”
Section: Resultssupporting
confidence: 67%
“…This result is generally in line with previous studies conducted in Mediterranean islands [33,[35][36][37] and for the first time reported concerning the Maltese population. Younger generations have been often reported to be less likely to follow a Mediterranean dietary pattern [38][39][40][41][42][43]. The globalization process and the so-called "Westernization" of the diets have led to a slow, yet growing abandonment of traditional dietary habits in the Mediterranean countries together with the introduction of high-calorie, nutrient-poor ultra-processed foods [44].…”
Section: Discussionmentioning
confidence: 99%
“…4.46 ± 3.63 4.10 ± 3.24 0.712 0.10 4.51 ± 3.78 2.98 ± 4.17 0.233 0.39 Salto de longitud (cm) 71.6 ±24.0 59.0 ± 27.1 0.081 0.50 69.4 ± 23.2 58.3 ± 25.3 0.158 0.46 Flamenco derecha (s) 14.2 ± 21.6 6.65 ± 9.18 0.281 0.31 13.5 ± 13.3 7.76 ± 7.16 0.126 0.50 Flamenco izquierda (s) 12.0 ± 15.4 11.2 ± 20.2 0.861 0.05 11.9 ± 15.5 8.12 ± 7.16 0.378 0.29 Gateo (s) 13.0 ± 3.19 16.8 ± 5.45 0.002 -0.92 14.0 ± 4.09 16.6 ± 6.70 0.130 -0.50 Velocidad 4x10 (s) 16.0 ± 2.13 15.4 ± 3.35 0.055 -0.55 16.7 ± 3.32 18.7 ± 3.46 0.077 -0.58 CN (nº de estadio) 2.19 ± 1.22 2.13 ± 1.35 0.854 0.05 2.24 ± 1.77 1.67 ± 0.81 0.244 0.38 ADM: Adherencia Dieta Mediterránea; CN: Course Navette; DMD: Dinamometría manual derecha; DMI: Dinamometría manual izquierda; ES: Effect Size -Tamaño del efecto; IMC: Índice de Masa Corporal; PC: Perímetro de la Cintura En un inicio, destaca como no existen sujetos con baja adherencia a la dieta mediterránea. Esto es un aspecto relevante, ya que, en estudios con muestras con una edad mayor, hay una tendencia a la presencia de este grupo (Cömert, Cerkez, Tekin, Aydogan & Essiz, 2015;Bibiloni, Pons & Tur, 2015;Barja-Fernández, Pino, Portela & Leis, 2019). Los motivos no se han analizado en el presente trabajo, aunque se ha evidenciado que según avanza la edad y los sujetos tienen mayor autonomía, suelen desarrollar hábitos menos saludables en cuanto a alimentación (Grosso, et al, 2013;Grao-Cruces, et al, 2013).…”
Section: Discussionunclassified